Social Sufism as the Basis of Religious Moderation: An Analysis of Amin Syukur's Thoughts on Social Ethics and Sufistic Leadership - Abdul Mun'em Choiri; Syaifullah Yazid (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
Abstract The phenomena of intolerance, radicalism, and moral degradation accompanying the tide of modernization underscore the importance of strengthening religious moderation in multicultural societies such as Indonesia. One relevant approach is social Sufism, which emphasizes a balance between individual piety and social responsibility, so that spirituality does not stop at the inner aspect but is manifested in the practice of communal life. This article examines Amin Syukur's thoughts on religious moderation through the perspective of social Sufism, highlighting Qur'anic values such as compassion, justice, tolerance, and ukhuwah (brotherhood) as the foundation of social harmony. This study uses a literature review method through an analysis of Amin Syukur's works and literature related to Sufism and religious moderation. The results of the study show that social Sufism places collective spirituality and Sufi leadership as effective models of social transformation in dealing with diversity. Values such as control of desires, awareness of Allah's supervision, and balance between spiritual and social aspects can shape public ethics. The concept of insan kāmil is also an ideal in social Sufism, as it describes a perfect human being who harmonizes spiritual, moral, and social dimensions for the common good. Other findings confirm that religious moderation as a form of transformative Sufism encourages pluralistic, inclusive, and open attitudes that are in line with the values of Pancasila and strengthen national social cohesion. Thus, the integration of spiritual values, social values, Sufi leadership, and the orientation of insan kāmil in Islam can be a constructive solution for building a peaceful, just, and civilized society amid plurality. Keywords: Social Sufism, Religious Moderation, Amin Syukur, Insan Kāmil.